Influences of compatibilization and compounding process on electrical conduction and thermal stabilities of carbon black‐filled immiscible polypropylene/polystyrene blends. Issue 2 (12th June 2012) - Xu, Chunfeng; Tan, Yeqiang; Song, Yihu; Zheng, Qiang
Abstract: The influences of styrene–butadiene–styrene (SBS) copolymer compatibilizer and compounding process on the electrical conduction and thermal stabilities of carbon black (CB)‐filled immiscible polypropylene (PP)/polystyrene (PS) (1/1) blends were investigated. The immiscible CB/PP/PS composite with CB homogeneously located in the PS phase exhibited the highest resistivity and the fastest variation amplitudes of electrical resistivity (ρ) and rheological parameters upon annealing. An optimal content of 5 vol% SBS could significantly lower ρ of the composites by partially trapping CB particles in the PP/PS interfacial region and by reducing the phase size. The compatibilizer markedly slowed down the variation amplitudes of ρ and rheological parameters and the phase coalescence of the composites submitted to thermal annealing. The (SBS/CB)/PP/PS composite with CB located at the PP/PS interface and in the PP phase prepared by blending a (SBS/CB) masterbatch with PP and PS exhibited lower ρ and better thermal stability in comparison with the CB/SBS/PP/PS composite with CB mainly within the PS phase and partially at the PP/PS interface prepared by direct blending. Spreading and wetting coefficients were used to explain the CB distribution and the phase morphology of the composites. © 2012 Society of Chemical Industry Abstract : Compatibilization and the compounding process influence the electrical conduction and thermal stabilities of carbon black (CB)‐filled immiscible polypropylene (PP)/polystyrene (PS) blends by changing the distribution of CB in the composites.